The usefulness of NEWS2 at day 7 of hospitalization in predicting COVID-19 evolution and as an early endpoint in therapeutic trials. Issue 2 (February 2021) - Sixt, Thibault; Moretto, Florian; Devilliers, Hervé; Abdallahoui, Maroua; Eberl, Isabelle; Rogier, Thomas; Duong, Michel; Salmon-Rousseau, Arnaud; Mahy, Sophie; Buisson, Marielle; Esteve, Clementine; Chavanet, Pascal; et al.
Highlights: There is a need for reliable tools to predict the evolution of hospitalized patients suffering from COVID-19. The likelihood of unfavourable evolution for patients hospitalized for COVID-19 with a National Early Warning Score 2 (NEWS2) below 7 at Day 7 of hospitalization is nearly non-existent. Such a score could thus be used to allow earlier discharge of the patients and as a judgement criterion in therapeutic trials.